Toponyms and Norms of the Georgian Literary Language - Apridonidze, Shukia (Actual Problems of Kartvelology, 2025)
Geographical names, such as the names of natural objects or settlements, are one of the most important issues among the normative problems of the literary language. We can highlight the following issues: 1. Names of sides of the country (west, east, etc.) used as adjectives within toponyms and hydronyms; 2. Spatial orientations according to the natural objects (mountains and waters) and their reflection in terminology and macrotoponymy; 3. Georgian names of countries and elements reflecting settlements within the Georgian territory (‘from the village to the world’); 4. Georgian terms referring to spatial parameters and their normative usage; 5. Issues concerning the translated and untranslated geographical names in complex toponymy.